PERAN KEPEMIMPINAN DAN MOTIVASI KERJA: MEMBANGUN KETAHANAN ORGANISASI UMKM DIMSUM KUSKUSSAN DI CIKARANG SELATAN DENGAN ADAPTASI ORGANISASI SEBAGAI VARIABEL MODERASI - Milda Noviani; Listya Zahra Shafa. M; Hotma Ernisa Dewi; Anisa Rahmawati; Retno Purwa Setyaningrum (Adiba Aisha Amira, 2026)
This study aims to analyze the influence of leadership and work motivation on organizational resilience in Dimsum KusKussan MSME, with organizational adaptability serving as a moderating variable. A qualitative approach was employed through semi-structured interviews with the business owner and employees. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that effective leadership and strong work motivation play an important role in supporting organizational resilience. Furthermore, organizational adaptability strengthens the business's ability to respond to environmental changes and market uncertainty. The ability to utilize digital media and adjust business strategies becomes a key factor in maintaining business sustainability. The study concludes that the synergy between leadership, work motivation, and organizational adaptability contributes significantly to the resilience and sustainability of Dimsum KusKussan MSME.